The Comparison of Antibacterial Efficacy, Cell Proliferation, and Wound Healing Properties in Extracts Derived from Leaves and Inflorescences of Hang Kra Rog Phu Phan ST1 (Cannabis sativa L.) - Khlongkhlaeo, Apitsada; Sookruksawong, Suchonma; Rattanasuk, Surachai (Trends in Sciences, 2024)
The therapeutic potential of Cannabis sativa extracts in wound healing applications has garnered significant interest due to their diverse pharmacological properties. This study aimed to comparatively evaluate the antibacterial properties and wound-healing activity of ethanolic extracts derived from C. sativa leaves and inflorescences of the Hang Kra Rog Phu Phan ST1 cultivar. The extracts were prepared using ethanol, and their antibacterial properties, cytotoxicity and ability to promote cell proliferation and migration were investigated. The antibacterial activity was assessed against Staphylococcus epidermidis TISTR 518, Klebsiella pneumoniae TISTR 1383, Pseudomonas aeruginosa TISTR 2370, Staphylococcus aureus TISTR 1466 and Bacillus cereus TISTR 2373 using the disk diffusion method and broth microdilution assay. Cell viability and proliferation were evaluated using the MTT assay on human fibroblasts in serum-supplemented and serum-depleted media. The scratch wound healing assay was employed to quantify cell migration and wound closure. The results demonstrated that both leaf and inflorescence extracts exhibited antibacterial activity, with the inflorescence extract showing higher efficacy against S. aureus. Furthermore, the extracts enhanced fibroblast proliferation and migration in a concentration-dependent manner. Notably, the leaf extract outperformed the inflorescence extract in promoting fibroblast proliferation and migration, particularly at earlier time points. These findings suggest that C. sativa extracts, particularly from the leaves, possess wound-healing properties and could be developed as novel therapeutic agents for promoting efficient wound repair and managing chronic non-healing wounds. HIGHLIGHTS This research is the inaugural exploration into the antibacterial properties and wound healing capabilities of the Cannabis sativa L. Hang Kra Rog Phu Phan ST1 cultivar, a unique variant of Cannabis sativa. This strain has received official recognition and registration from the Rajamangala University of Technology Isan, Thailand. Our findings reveal that extracts derived from the leaves and inflorescences of the Hang Kra Rog Phu Phan ST1 strain display potent antibacterial activity against five tested pathogenic bacteria, namely Staphylococcus epidermidis TISTR 518, Klebsiella pneumoniae TISTR 1383, Pseudomonas aeruginosa TISTR 2370, Staphylococcus aureus TISTR 1466, and Bacillus cereus TISTR 2373. Moreover, these extracts stimulate the growth and movement of human fibroblasts. These compelling results underscore the potential for harnessing this plant as an efficacious agent for wound healing. GRAPHICAL ABSTRACT